Granulation compared to co-application of biochar plus mineral fertilizer and its impacts on crop growth and nutrient leaching - Jannis Grafmüller; Jens Möllmer; E. Marie Muehe; Claudia I. Kammann; Daniel Kray; Hans-Peter Schmidt; Nikolas Hagemann (Scientific Reports)
Abstract Mechanized biochar field application remains challenging due to biochar’s poor flowability and bulk density. Granulation of biochar with fertilizer provides a product ready for application with well-established machinery. However, it’s unknown whether granulated biochar-based fertilizers (gBBF) are as effective as co-application of non-granulated biochar with fertilizer. Here, we compared a gBBF with a mineral compound fertilizer (control), and with a non-granulated biochar that was co-applied at a rate of 1.1 t ha−1 with the fertilizer in a white cabbage greenhouse pot trial. Half the pots received heavy rain simulation treatments to investigate nutrient leaching. Crop yields were not significantly increased by biochar without leaching compared to the control. With leaching, cabbage yield increased with gBBF and biochar-co-application by 14% (p > 0.05) and 34% (p < 0.05), respectively. Nitrogen leaching was reduced by 26–35% with both biochar amendments. Biochar significantly reduced potassium, magnesium, and sulfur leaching. Most nitrogen associated with gBBF was released during the trial and the granulated biochar regained its microporosity. Enriching fertilizers with biochar by granulation or co-application can improve crop yields and decrease nutrient leaching. While the gBBF yielded less biomass compared to biochar co-application, improved mechanized field application after granulation could facilitate the implementation of biochar application in agriculture.